HUBUNGAN UMUR DAN JENIS KELAMIN DENGAN ANGKA KEJADIAN KATARAK SENILIS DI RS CAMATHA SAHIDYA - Amelia Eka Damayanti; Yani Christina (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2023)
Background: Cataract is a disease with clouding of the lens, the cause of cataract is a multifactorial disease. The results of a data survey in 2020 at Camatha Sahidya Hospital, at least 42 people have had surgery for senile cataracts. Based on the survey data, researchers are interested in researching the relationship between age and gender with the incidence of senile cataracts at Camatha Sahidya Hospital, Batam City in 2021. Method: The method of this study was Observational Analytical with a Cross-Sectional approach carried out at Camatha Sahidya Hospital with a total sample of 65 people taken using a purposive sampling technique. The research results were analyzed by Chi-Square Test. Result: The results of the Chi-Square Test show that there is a relationship between age with the incidence of senile cataracts at Camatha Sahidya Hospital, Batam City in 2021 with a p value = (p≤0.05). Whereas for the gender variable, there is no relationship with the incidence of senile cataracts with a p value = (p> 0.05). Conclusion: Based on the results of this study it can be concluded that there is a relationship between age with the incidence of senile cataracts and there is no significant relationship between gender and the incidence of senile cataracts at Camatha Sahidya Hospital, Batam City in 2021.